AN INTERNATIONAL FINANCIAL CENTER. WHO BENEFITS? - M. K. Belyaev (Модернизация, инновация, развитие, 2016)
In recent decades we can see the rise of global financial centers on the wave of globalisation of financial operations. Alongside with traditional centers with a long history some new centers formed. What advantages get companies working in such centers and firms buying its services?What advantages gets the recipient country? These issues are in the centre of the article.